Low dystrophin variability between muscles and stable expression over time in Becker muscular dystrophy using capillary Western immunoassay - Z. Koeks (Nature Portfolio, 2021)
Abstract Becker muscular dystrophy (BMD) is the milder allelic variant of Duchenne muscular dystrophy, with higher dystrophin levels. To anticipate on results of interventions targeting dystrophin expression it is important to know the natural variation of dystrophin expression between different muscles and over time. Dystrophin was quantified using capillary Western immunoassay (Wes) in the anterior tibial (TA) muscle of 37 BMD patients. Variability was studied using two samples from the same TA biopsy site in nine patients, assessing nine longitudinal TA biopsies, and eight simultaneously obtained vastus lateralis (VL) muscle biopsies. Measurements were performed in duplicate with two primary antibodies. Baseline dystrophin levels were correlated to longitudinal muscle strength and functional outcomes. Results showed low technical variability and high precision for both antibodies. Dystrophin TA levels ranged from 4.8 to 97.7%, remained stable over a 3–5 year period, and did not correlate with changes in longitudinal muscle function. Dystrophin levels were comparable between TA and VL muscles. Intra-muscle biopsy variability was low (5.2% and 11.4% of the total variability of the two antibodies). These observations are relevant for the design of clinical trials targeting dystrophin production, and may urge the need for other biomarkers or surrogate endpoints.